2012
DOI: 10.1021/ef301343q
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Effects of Particle Shape and Operating Conditions on Combustion Characteristics of Single Biomass Particles

Abstract: An experimental study is performed to investigate the ignition, devolatilization, and burnout of single biomass particles of various shapes and sizes under process conditions that are similar to those in an industrial combustor. A chargecoupled device (CCD) camera is used to record the whole combustion process. For the particles with similar volume (mass), cylindrical particles are found to lose mass faster than spherical particles and the burnout time is shortened by increasing the particle aspect ratio (surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 23 publications
2
64
0
Order By: Relevance
“…The temperatures in large scale pulverized fuel furnaces are in a similar range and, while oxygen concentration varies depending on fuel/air mix and position in the flame, this is also not unrepresentative. An extension to the experiment may consider creating different oxygen conditions as has been achieved in othersÕ experiments using alternative apparatus [15].…”
Section: Combustion Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperatures in large scale pulverized fuel furnaces are in a similar range and, while oxygen concentration varies depending on fuel/air mix and position in the flame, this is also not unrepresentative. An extension to the experiment may consider creating different oxygen conditions as has been achieved in othersÕ experiments using alternative apparatus [15].…”
Section: Combustion Apparatusmentioning
confidence: 99%
“…furnace. However there have been a number of experimental methods documented which examine combustion behaviour of biomass particle dimensions in the order of 1mm [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…sphericity, symmetry and aspect ratio) by using one of the discussed techniques. Various biomass shapes result in different volume-to-surface area ratios which determine heat and mass transfer [44,9]. A spherical particle, as commonly used in literature [45], has a higher volume to surface area ratio than a cylindrical particle of the same volume.…”
Section: Discussionmentioning
confidence: 99%
“…Momeni et al [10] conducted the experiments for a combustion process of a single biomass particle in a combustion chamber. Their results showed that the particle combustion process is influenced by the shape and the size of the particle (the particle aspect ratio), the oxygen concentration and the temperature.…”
Section: Residence Timementioning
confidence: 99%